A pair of new neo-clerodane diterpenoid epimers from the roots of Croton crassifolius and their anti-inflammatory. Issue 20 (17th October 2020) - Zhang, Dong-Bo; Tang, Zhi-Shu; Xie, Pei; Liang, Yan-Ni; Yu, Jin-Gao; Zhang, Zhen; Duan, Dong-Zhu; Cui, Chun-Li; Song, Zhong-Xing; Ren, Li; Wang, Zheng; Yu, Dao-Geng
Abstract: A pair of new neo- clerodane diterpenoid epimers, 3 S -methoxyl-teucvin (1 ) and 3 R -methoxyl-teucvin (2 ), were isolated from the Roots of Croton crassifolius. Their structures were completely established on the basis of spectroscopic methods, and the absolute configurations were determined by analysis of electronic circular dichroism (ECD) spectroscopy and X-ray diffraction analysis. Compounds 1 and 2 exhibited anti-inflammatory activities with IC50 values of 0.82 and 0.54 μM, respectively, while the IC50 value of dexamethasone as a positive control was found to be 0.14 μM. Graphical abstract: